2021
DOI: 10.1177/0003134821998686
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease and Idiopathic Lung Fibrosis. From Heartburn to Lung Transplant, and Beyond

Abstract: Idiopathic pulmonary fibrosis (IPF) and gastroesophageal reflux disease (GERD) are undoubtedly related. Even though it is not clear yet which one is the primary disease, they certainly interact increasing each other’s severity. Symptoms are unreliable to diagnose GERD in patients with IPF, and objective evaluation with pH monitoring and/or bronchoalveolar lavage analysis is mandatory. Pharmacological treatment with proton pump inhibitors (PPIs) may bring control of IPF in few patients, but PPIs do not control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The presence of associated cardiovascular diseases can cause and intensify the chest pain in patients with IPF (45). IPF is also linked to GORD, which can cause discomfort or burning in the chest (46,47). Chronic pain has biological, psychological, and societal consequences.…”
Section: • Other Painful Conditionsmentioning
confidence: 99%
“…The presence of associated cardiovascular diseases can cause and intensify the chest pain in patients with IPF (45). IPF is also linked to GORD, which can cause discomfort or burning in the chest (46,47). Chronic pain has biological, psychological, and societal consequences.…”
Section: • Other Painful Conditionsmentioning
confidence: 99%
“…Also, a study including over 100,000 participants revealed the prevalence of pulmonary fibrosis is significantly higher than that of healthy controls [ 15 ]. Recently, some studies have suggested that the acid inhalation caused by GERD may be associated with pulmonary fibrosis, while pulmonary diseases may promote an altered transdiaphragmatic pressure gradient and cause GERD [ 16 , 17 ]. However, the underlying mechanism between IPF and GERD still remains ambiguous and needs further exploration.…”
Section: Introductionmentioning
confidence: 99%